AL-QALB AS THE CORE ELEMENT OF THOUGHT AND ACTION: A LITERATURE REVIEW - Muhammad Zickryl Hakim Roslan,; Nor Hanani Ismail,; Mohamad Khadafi Hj. Rofie, (Journal of Islamic, Social, Economics and Development, 2023)
In Islam, al-Qalb (heart) is described as a tool of thinking and storing of knowledge. Terms such as tafaqquh, ta’aqul are connected to the word al-Qalb. In addition, al-Qalb is also associated with a person’s intention or determination before taking actions and making decisions. Those who are given wisdom or intelligence also use al-Qalb to think. These descriptions give rise to one question. What do the scholars discuss on the concept of al-Qalb as the core element of thought and action? The paper aims to analyse the highlights of al-Qalb-related works using content analysis. This study showcases the concept of al-Qalb as the core element of thought and action.